Determinants of team effectiveness among young researchers in a Malaysian public university - Alby, Jeffrey Lawrence D'Silva; Abu Samah, Asnarulkhadi; Ortega, Adriana; Sulaiman, Abdul Hadi (Human Resource Management Academic Research Society, 2017)
Without a doubt in this era of globalization and borderless world, working in teams leads towards higher output and productivity. However, in the context of higher education settings especially among researchers, it was found that the work culture is very much aligned towards individualism efforts. Thus, the main aim of the study is to determine the influence of task interdependence and task conflict on team effectiveness. This is a quantitative study and the data was collected from 181 respondents from a local research university in Malaysia. The study found that team interdependence and task conflict contributed 22% of the variances in team effectiveness. Some suggestions are put forward to improve team effectiveness in institutions of higher learning.